Didelio meistriškumo plento dviratininko rengimo monitoringas metiniu ciklu - Konovalovas, I.; Milašius, K. (Sporto Mokslas-Sport Science, 2020)
Cycling is one of the most popular means of physical activity among people of all ages, from children to seniors. At the same time, it appears to be a very popular competitive sport, also remaining one of the most complex sports in its content, where athletes are required to employ the whole set of their abilities. Excellence of road cyclists is mostly dependent on aerobic and anaerobic endurance and muscle power in various energy zones. Most of the cyclists` results are determined by consistent workout planning during the annual training cycle, which is a complex pedagogical process including various structural, physiological, mental and adaptive processes taking place in athlete`s body. Thus, high requirements for training program accuracy are raised, aiming to ensure proper training of functional and physical capacities of an athlete. Road cyclists are characterized by high aerobic capabilities - high maximal oxygen uptake VO2max and the ability to maintain it for a long time. VO2max determines the athlete`s ability to maintain speed in the distance and to carry out great aerobic training volume. A review of a number of scientific publications on the training of elite cyclists, as well as observation of the change of these athletes` physical and functional capacity during annual training cycle reveals that most articles focus on one certain aspect of training. Although our research includes the ones having focused on road cyclists training, there is still a lack of research to address the issue of high-performance cyclists` training in Lithuania.The aim of the study is to summarize the preparation of the Lithuanian cyclist I.K. for the World Championship during his annual training cycle, as well as to carry out monitoring of the issues of his training, physical and functional capacity. Study organization and methods. The paper summarizes the structure and content of the elite road cyclist`s preparation for the World Championship, his physical and functional capacity changes in the annual training cycle. Three studies were conducted: 1st at the beginning of the preparatory period; 2nd in the middle of the competition period; 3rd at the end of the competition period. Muscle power in different energy zones was investigated and athlete`s aerobic capacity was determined. Functional capacity of the cardiovascular system (FCCS) was assessed by resting pulse rate and Roufier index data. Our research showed that the training process of our investigated road cyclist was well organized and it was mainly carried out by a team of bicycle professionals from abroad. Training time compiled 921 hours a year and 855 hours were spent working on the road, which covered 27.582 km of cycling. This corresponds to the minimum standards recommended for elite cyclists. Monitoring the cyclist`s muscle power over the annual cycle shows that these levels in the various energy zones were in line with those of elite cyclists and tended to increase during the annual cycle. The cyclist`s aerobic capacity at critical intensity, lactate and anaerobic ventilation thresholds used to increase from the beginning of the preparatory period to the end of the competition period. VO2max increased from 69.2 to 72.9 ml/min/kg and oxygen consumption at the anaerobic metabolic threshold was 60.4 ml/min/kg, accounting for 82.9% of VO2max. The performance of Lithuanian cyclist in national, international and world championship competitions can be well appreciated. The athlete continues his sporting career in the top cycling league ProTour.